(untitled) (Scientific journal of the Fergana State University, 2026)
This article provides an in-depth analysis of the socio-philosophical interpretation of the category of spiritual practice, revealing its essence, content, and functional significance in modern society from a philosophical perspective. Spiritual practice is understood as an integral connection between a person’s inner world, faith, moral choice, and social activity. The study compares and analyzes the views of Eastern philosophers - in particular, al-Farabi, Ibn Sina (Avicenna), and al-Ghazali - with the axiological and existential approaches of Western philosophy. The article substantiates the role of spiritual practice in ensuring personal perfection, strengthening social stability, and renewing social consciousness. At the same time, the practical forms of spirituality - religious, moral, and cultural activity - are interpreted as decisive factors in forming the spiritual foundation of social development. The research findings contribute to the philosophical reconsideration of the role and significance of spiritual practice within the context of modern globalization processes.